Evading death and rejecting heroism (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
The death of the main character in the mock-heroic poem is quite an unusual event: even considering such works as grotesque and ridiculous poems and the parodies of classical myths as part of this literary production, the list of the heroes who fall bravely on the battlefield remains quite short. It is not by chance: except for those characters who literally die bursting with laughter, or those who die from the pinch of a small crab, heroes of mock-heroic poems are cowards, reluctant to heroism, who, above all, aim to stay alive to keep bingeing on food, making love, and enjoying their lives. The very idea of heroism is constantly criticized and derided. This desire for life against the duty of self-sacrifice – in the Counter-Reformation culture – is more political than literary critics have generally thought. A look at the works of writers such as Aretino, Folengo, Tassoni, Lippi, de’ Bardi, Corsini, as well as Traiano Boccalini, provides the evidence of the existence, in Sixteenth-Seventeenth century culture, of a mentality alternative to the dogmas of aristocratic society.
Keywords: Mock-heroic poem; hero; heroism; death of the hero